A Novel Trajectory of C7 Laminar Screws Determined Using Three-Dimensional Computed Tomography and Surgical Simulation Software: Comparison with a Pre-existing Trajectory - Chee Kean Lee; Quan You Li; Jiwon Park; Sang-Min Park; Ho-Joong Kim; Bong-Soon Chang; Byungjun Woo; Jin S. Yeom (Asian Spine Journal, 2023)
Study Design Examination using three-dimensional screw trajectory software and computed tomographic scans. Purpose To evaluate the feasibility of a novel trajectory for C7 laminar screws and to compare it with an old trajectory. Overview of Literature The previously reported trajectory of C7 laminar screws has a horizontal direction without a fixed target point. Our new trajectory has a cephalad direction with a fixed target point. Methods Computed tomographic scans of a total of 50 male and 50 female patients were utilized. The placement of C7 laminar screws was activated employing the new and old trajectories. The success rate, the causes of failure, and the maximum allowable length of each trajectory were compared. Results Employing the new trajectory, the success rates of the unilaminar and bilaminar screws were 93% and 83%, respectively, which were significantly better than the old trajectory (80%, p<0.0001 and 70%, p=0.0003). The most prevalent cause of failure was laminar cortical breach followed by facet joint violation. The new trajectory also offered significantly longer maximum allowable screw length in unilaminar (32.5±4.3 mm vs. 26.5±2.6 mm, p<0.001), bilaminar cephalic (29.5±3.8 mm vs. 25.9±2.6 mm, p<0.0001) and bilaminar caudal (33.1±2.6 mm vs. 25.8±3.1 mm, p<0.001) screws than the old trajectory. With the new and old trajectories, 70% vs. 6% of unilaminar, 60% vs. 2% of bilaminar caudal, and 32% vs. 4% of bilaminar cephalic screws could be protracted perfectly into the corresponding lateral mass without any laminar cortical or facet joint violation (p<0.0001). Conclusions The novel trajectory possesses a substantially higher success rate, longer maximum allowable screw length, and higher chance to be extended into the lateral mass (a condition known as a lamino-lateral mass screw) than the old trajectory.